DISTRIBUTION OF CORAL COMMUNITIES ON REEF SLOPES IN THE MASCARENE ARCHIPELAGO, INDIAN OCEAN - Faure, Gerald (Marine Research in Indonesia, 1977)
Three zones and sic "horizons" are defined and described on the basis of topographic elements, growth forms of corals, generic and specific diversity of scleractinians and associated fauna and flora - : Spurs and grooves zone of coral-built morphogenesis ("horizon superieur" 0-5m, "horizon intermediaire" 5-15m, "horizon inferieur" 15-20m); Spurs and grooves of volcanic morphogenesis 20-25m; Volcanic flagstone ("horizon superieur" 25-30m, "horizon moyen" with sponges and corals, 30-35m, "horizon inferieur" with gorgonians and antipatharia 35-50m). A total of 98 species belonging to 58 genera were collected on reef slopes. It was found that there is a successive increase in generic and specific diversity from the upper part (36 species), to 20 meters (63 species), related to the decrease of exposure to wave action. The decrease in the number of species from 25 (54 species) to 50 meters (?18 species), proves that light becomes a limiting factor below 25-30m. Nevertheless, sedimentation effects, biological competition (algae, sponges, alcyonarians?.) and other factors are very significant in determining community structure of corals. A comparative study (quantitative and qualitative distribution, zonation) with other localities is suggested as conclusion.